Covalent Immobilization of Protein A on Chitosan and Aldehyde Double-Branched Chitosan as Biocompatible Carriers for Immunoglobulin G (Igg) Purification. (31st July 2018) - Khodaei, Simin; Ghaedmohammadi, Samira; Mohammadi, Mehdi; Rigi, Garshasb; Ghahremanifard, Parisa; Zadmard, Reza; Ahmadian, Gholamreza
Abstract: High-affinity ligands, such as protein A, can be used to develop biocompatible matrices for antibody purification. In this paper, two methods were used for immobilization of protein A on the chitosan. In the first approach, amino groups of chitosan beads were functionalized with tris(2-aminoethyl)amine to produce amine double-branched moieties, which were subsequently activated with glutaraldehyde. In the second approach, chitosan beads were directly modified by glutaraldehyde to produce aldehyde groups. Structural characterization and successful modification of the functional groups on the supports were confirmed by scanning electron microscopy, FTIR spectroscopy and elemental analysis. Covalent immobilization of protein A was then performed on the surface of both supports. The immobilization yield was determined by using fluorescence spectroscopy, showing almost 15% increased capacity for the double-branched derivatized chitosan. The Immunoglobulin G (IgG) purification ability of the double-branched support was also almost 1.7-fold higher than the monoaldehyde derivative at the same condition.